Bio-physicochemical markers of the Aedes aegypti breeding water in endemic and non-endemic area - Nurul Hidayah; Dwi Rahmawati (International Journal of Public Health Science (IJPHS), 2019)
The survival of Aedes aegypti larvae is inseparable from the adequacy of food, including organic substances available in the breeding water. It is very dependent on the level of water markers such as temperature, salinity, Dissolved Oxygen, and pH. The study used quantitative observational analytic with a case-control study design. Case group has consisted of breeding water in endemic area and control group was in non-endemic area. The sample size was 43 samples for each group, collected by purposive sampling technique. Data were analyzed by Chi-square and Mann-Whitney test. Larvae mostly presence in endemic area (68.3%) and mostly absent in non-endemic area (85.4%) (p-value = 0.002). Temperature in endemic area mostly in 27-30oC (86%) and non-endemic area mostly in <27oC or >30oC (72.1%) (p-value = 0.000). Salinity in endemic and non-endemic areas has no difference (p-value = 0.266). DO in endemic areas were mostly in 5.02-7.82 mg/l (76.7%). While DO in non-endemic area was mostly in <5.02 mg/l or >7.82 mg/l (95.3%) (p-value = 0.001). The pH <6 or >7.8 is mostly in non-endemic areas (87.8%) and pH 6-7.8 is mostly in endemic areas (63.4%) (p-value = 0.000). Bio-physicochemical markers of breeding sites water have differences between endemic and non-endemic area except salinity. The temperature, salinity, DO, and pH affected the presence of larvae and the most affected is DO marker. While the marker that affected the presence of larvae in the non-endemic area is pH.